Assessment of Dental Calculus, Plaque and GingivalInflammation in Patients with Urinary Stone - Mohammed, Maher B; Mahmood, Maha Sh. (Journal of Baghdad College of Dentistry, 2019)
Background: Dental calculus is mineralized dental plaque formed on teeth and dental prosthesis surfaces in the oral cavity. Urinary stone is a crystal aggregation formed in urinary system due to minerals saturation present in urine. The structure of dental calculus is similar to that of urinary stone. Objective: To assess oral hygiene and gingival status in patients with urinary stone. And compared with healthy subjects. Patients and Methods: Sixty participants, 25-40 years, were involved in this study who were divided into study and control group. The study group involved patients with urinary stone while the control group involved healthy subjects. Clinical parameters including plaque, calculus and gingival indices were recorded for all participants. The correlation between the recorded clinical parameters was estimated. Results: The study group mean (±SD) plaque (1.435±0.499), gingival (0.995±0.288) and calculus (1.28 ±0.66) indices were found to be significantly high compared with control group(0.868±0.265), (0.602±0.265) (0.501±0.457 ) respectively. The formed calculus was positively associated with accumulated plaque (r: 0.608, p < 0.05) and gingival inflammation(r: 0.612, p < 0.05). Conclusion: Urinary stone patients were associated with more plaque and calculus accumulation, and had worse gingival inflammation compared to healthy participants. Thus, they need to be more aware of their gingival health status and improved preventive care of oral health.